Phytotoxicity and allelopathic potential of Juglans regia L. leaf extract - Đorđević, Tijana; Đurović-Pejčev, Rada; Stevanović, Marija; Sarić-Krsmanović, Marija; Radivojević, Ljiljana; Šantrić, Ljiljana; Gajić-Umiljendić, Jelena (Frontiers in Plant Science, 2022)
Implementation of plant extracts that are rich in phytochemicals and have allelopathic potential for weed management could enable reductions in the use of chemical herbicides. The present study investigated the herbicidal potential of walnut (Juglans regia L.) leaf extract (WLE) against two weeds, Amaranthus retroflexus L. and Chenopodium album L., by testing in vitro their seed germination and seedling growth, and then evaluating in vivo the oxidative stress of plants growing in pots. Effects of the walnut leaf extract was also tested on maize (Zea mays L.) in order to eliminate possible negative impact on a cultivated plant. Total phenolic acids and total flavonoid content in the extract were determined in prior bioassays, followed by separation and analysis of flavonoids and phenolic acids by high-performance liquid chromatography (HPLC). Phytochemical analysis revealed that the obtained extract is notably rich in phenolic compounds, while HPLC analysis confirmed the presence of (+)-catechin, luteolin, myricetin, rutin, (-)-epicatechin, genistin, protocatechuic acid and caffeic acid as major extract components. The results obtained in bioassays revealed a significant negative impact of the walnut leaf extract on germination and seedling growth of the tested weeds, as well as significant oxidative stress in weeds grown in pots. Although it affected maize seedling growth in vitro in a similar manner as the tested weeds, maize germination was less sensitive to treatment, and the extract did not have a significant negative impact in terms of oxidative stress in maize plants growth in pots. The findings show that walnut leaf extract may have a promising role in replacing chemical herbicides in maize.